STEAM TURBINE HEAT RATE ANALYSIS BY METHOD PERFORMANCE TESTS ON POWER PLANT IN PT. KSA PALM FACTORY - Khusnaini, Alfan; Aspiansyah, Aspiansyah; Harianto, Agus; Adrianur, Halim (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
This research analyzed the heat rate of a steam turbine in the palm factory of PT. KSA (PT. KSA) using performance testing methods. Steam turbine heat rate is a crucial parameter in power plant efficiency, and optimizing it can lead to significant cost savings. The research methodology conducted performance tests on the steam turbine at KSA's palm factory. The collected data was analyzed to determine the rate of improvement. The efficiency of a steam turbine can be seen from the heat energy input to produce 1 kWh of electricity and the turbine heat rate. Steam turbine efficiency was compared with the fuel energy required for every 1 kWh with the turbine heat rate. The turbine heat rate value was obtained based on the performance test, with the highest value being 51.516 (kJ/kWh) and the lowest being 40.514 (kJ/kWh). For steam turbine efficiency, the highest value was 8.89%, and the lowest value was 6.99%.